A tale of two cafés: spatial production as de facto language policy. Issue 5 (20th October 2021) - Cook, William Robert Amilan
ABSTRACT: This paper investigates the production of space and language policy in Ras Al Khaimah, a city in the United Arab Emirates. The paper builds on recent work in socio- and applied linguistics that has made use of sociospatial concepts from human geography. It argues that researchers should not only investigate space as a factor structuring language practices, but should also explore how space is produced and how this production generates de facto language policy (Shohamy, E. G. (2006). Language policy: Hidden agendas and new approaches . Routledge). The paper draws on Lefebvre's [1991. The production of space (D. Nicholson-Smith, trans.). Basil Blackwell Ltd. (Original work published 1974)] spatial triad ( spatial practice, representations of space, and representational spaces ) and utilizes ethnographic data to unpack the material, conceptual and symbolic production and maintenance of two Ras Al Khaimah cafés: a small café situated in a working-class South Asian part of the city and an upmarket café embedded in a semi-gated community for Western residents. It investigates how divergent de facto language policies emerge in each space from mechanisms of spatial production and explores how those mechanisms (and therefore the emergent language policies) are entangled with racism and socioeconomic inequality.